Muhammadiyah Covid-19 Islamic Boarding School: A Complete Self-Isolation Model With Neurospritual and Psychosocial Approaches - Mohammad Jailani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The purpose of this study was to analyze the Covid-19 Muhammadiyah Islamic boarding school with the complete independent isolation model. The subjects of this study consisted of Covid-19 patients and leaders of Covid-19 Islamic boarding schools. This research uses a qualitative approach with a case study type. This research was conducted at the Covid-19 Muhammadiyah Islamic Boarding School in Yogyakarta, which was located at the PKU Muhammadiyah Hospital in Yogyakarta. Data collection techniques using direct interviews, observation and documentation. The data analysis technique followed the Miles and Huberman model, namely data display, data reduction, and data verification. The validity of the data using triangulation. The results showed that the approach model used was complete self-isolation, on psychosocial and neurospiritual aspects. With the development of social relations on the psychosocial aspects, patients feel healthy and not stressed. As for the increase in priests and spiritual neurospiritual perspectives, it helps the immunity of Covid-19 patients to remain stable and their good deeds are better. This research has implications for Covid-19 patients in repairing and coaching related to social behavior and religious behavior during the Covid-19 period. Tujuan penelitian ini menganalisis pesantren Covid-19 Muhamamdiyah dengan model Isolasi mandiri paripurna. Subjek penelitian ini terdiri dari pasien Covid-19 dan pimpinan pesantren Covid-19. Penelitian ini menggunakan pendekatan kualitataif jenis studi tudi kasus. Penelitian ini dilakukan di pesanren Covid-19 Muhamamdiyah Yogyakarta yang bertempat di Rumah sakit PKU Muhammadiyah Yogyakarta. Teknik pengumpulan data menggunakan metode wawancara langusng, observasi dan dokumentasi. Teknik analisis data mengikuti model Miles dan Huberman yaitu display data, reduksi data, dan verifikasi data. Keabsahan data menggunakan triangulasi. Hasil penelitian menunjukkan bahwa model pendekatan yang diguanakn isolasi mandiri paripurna, pada aspek psikososial dan Neurospiritual. Dengan adanya pembinaan hubungan sosial pada aspek psikososial pasien merasa sehat dan tidak stress. Adapun peningkatan imam dan spiritual perpespektif neurospiritual membantu imun pasien Covid-19 tetap stabil dan lebih baik amal sholehnya. Penelitian ini berimplikasi terhadap pasien Covid-19 dalam perbaikan dan pembinaan yang berhubungan dengan prilaku sosial dan prilaku beragama di masa Covid-19.